TRANSLATION METHOD USED IN DELI MALAY AND SERDANG MALAY FOLKLORES FROM INDONESIAN TO ENGLISH - RIA RESTIKA; MASITOWARNI SIREGAR; LIDIMAN SAHAT M SINAGA (State University of Medan, 2021)
This study aimed to determine the many types of translation methods, how they were employed in the translation of the folklores